2020
DOI: 10.1142/s1793545820500224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibacterial photodynamic therapy on Streptococcus mutans plaque biofilm in vitro

Abstract: The main objective of this study is to evaluate the antibacterial effect of antibacterial photodynamic therapy (aPDT) on Streptococcus mutans (S. mutans) biofilm model in vitro. The selection of photosensitizers is the key step for the efficacy of photodynamic therapy (PDT). However, no studies have been conducted in the oral field to compare the functional characteristics and application effects of PDT mediated by various photosensitizers. In this research, the antibacterial effect of Methylene blue (MB)/650[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…Paramanantham et al reported that APDT with the PS malachite green inhibits the growth of S. aureus biofilms by up to 80% [ 27 ]. Streptococcus mutans , which is responsible for forming dental biofilms, is also effectively suppressed by APDT [ 31 ]. E. faecalis, which causes endodontic infections, is another example of the use of APDT against Gram-positive bacteria [ 32 ].…”
Section: Apdt Targeting Diseases and Organismsmentioning
confidence: 99%
“…Paramanantham et al reported that APDT with the PS malachite green inhibits the growth of S. aureus biofilms by up to 80% [ 27 ]. Streptococcus mutans , which is responsible for forming dental biofilms, is also effectively suppressed by APDT [ 31 ]. E. faecalis, which causes endodontic infections, is another example of the use of APDT against Gram-positive bacteria [ 32 ].…”
Section: Apdt Targeting Diseases and Organismsmentioning
confidence: 99%
“…As previously mentioned, the tooth enamel demineralization and dental caries is initiated through the production of organic acids such as lactic acid by microbial plaques. aPDT can reduce and inhibit the tooth enamel demineralization and dental caries via suppuration of the lactic acid production capacity in S. mutans biofilms [ 59 , 60 ]. In this study, lactate dehydrogenase calorimetry was employed to assay the lactate concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The carious potential of this bacterium is accentuated by the ability to secrete glucan (which promotes bacterial adhesion and biofilm formation) and lactic acid, also by its acid tolerance mechanism [ 19 ]. Previous studies evaluated PDT’s efficacy on S. mutans biofilms incubated for 5 days [ 4 , 7 ], 3 days [ 20 ], 48 h [ 21 ], respectively, while others [ 22 ] used a 7-day old biofilm. Our streptococcal biofilm also visibly developed on prepared teeth after 8 days.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the photosensitizer (MB) and laser power (100 mW) was based on previous works that demonstrated their efficacy [ 4 , 21 , 30 ]. MB had also a higher sterilizing effect [ 20 ] when compared with hematoporphyrin monomethyl ether (HMME). Post-PDT SEM images revealed a significant bacterial reduction; our results are in consensus with the antibacterial effect reported by other studies [ 4 , 6 , 20 , 21 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation